Efficacy of Intravitreal rAAV2-ND4 Injection in Treated Versus Fellow Eyes with Leber’s Hereditary Optic Neuropathy: A Meta-Analysis - Amr K. Hassan (10808070) (2024)
To compare the outcomes of rAAV2-ND4 injection in treated versus fellow eyes with Leber’s hereditary optic neuropathy (LHON). The protocol was pre-registered on PROSPERO (CRD42023441669). PubMed, Ovid MEDLINE, Cochrane CENTRAL, Google Scholar, Embase, CrossRef, OpenAlex, and Web of Science were reviewed from 1990–2023. Our analysis included 358 eyes of 307 patients. Of them, 256 (83%) patients received unilateral injections while 51 (17%) received bilateral injections. The mean age was 32 years. Baseline visual acuity (VA) of unilaterally injected eyes was 1.62. At 1 year, it was 1.6 compared to 1.4 (p = 0.002) in noninjected eyes. Baseline VA of bilaterally injected eyes was 1.6 and postoperatively at 1.5 years, it became 1.3 (p = 0.003). rAAV2/2-ND4 intravitreal injections showed no major differences in terms of improving visual acuity between treated and untreated eyes of the same patient. However, larger prospective RCTs, especially concerning OCT parameters, and visual field, are recommended to provide a better understanding and comparison. Other Information Published in: Neuro-Ophthalmology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01658107.2024.2360413